2021
DOI: 10.1186/s40708-021-00141-5
|View full text |Cite
|
Sign up to set email alerts
|

EEG-based human emotion recognition using entropy as a feature extraction measure

Abstract: Many studies on brain–computer interface (BCI) have sought to understand the emotional state of the user to provide a reliable link between humans and machines. Advanced neuroimaging methods like electroencephalography (EEG) have enabled us to replicate and understand a wide range of human emotions more precisely. This physiological signal, i.e., EEG-based method is in stark comparison to traditional non-physiological signal-based methods and has been shown to perform better. EEG closely measures the electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Entropy, in general, has proven to be a practical function in extracting meaningful information from raw brain waves (see Ref. 45 for an overview and definitions of entropy). However, a significant difference is that in our experiment, the dynamic variables calculated from the collected data, including entropy, were parameterized by the ambient temperature (thermostat).…”
Section: Methodsmentioning
confidence: 99%
“…Entropy, in general, has proven to be a practical function in extracting meaningful information from raw brain waves (see Ref. 45 for an overview and definitions of entropy). However, a significant difference is that in our experiment, the dynamic variables calculated from the collected data, including entropy, were parameterized by the ambient temperature (thermostat).…”
Section: Methodsmentioning
confidence: 99%
“…This approach achieved a higher classification accuracy than using all channels or a random subset of channels. Patel and Patel [48] used a combination of mutual information, correlation coefficient, and principal component analysis to rank the channels, and then used a genetic algorithm to select the best subset of channels. They also achieved higher accuracy than using all channels or a random subset of channels.…”
Section: Eeg-based Signal Extraction For Emotion Recognitionmentioning
confidence: 99%
“…In a review [1], it was concluded that the spectral entropy is among the best entropy measures to perform in this task. Also different entropy measures, including the spectral entropy, are used to classify emotions from EEG in a brain-computer interface, see recent review [15]. Additionally, applied to local field potential measurements, correlation of time varying spectral entropies is used to detect synchrony in neural networks [10].…”
Section: Spectral Entropymentioning
confidence: 99%